Empowering Women Through Decoupage Skills and Legal Education on Consumer Protection in Creative Businesses - Syam, Hasnidar; Ma’ruf, Tri Abriana; Khalik, Galang Nur; Aini, Lutfiah Qur Ratu (Advances in Community Services Research, 2026)
Purpose: This Community Service (PkM) activity aims to empower the Padeci business group from the PKK Women's Team in Padanglampe Village by strengthening their creative skills through decoupage techniques and increasing their legal literacy in consumer protection. This program is designed to encourage the creation of skilled, creative women who can increase their family income. Research Design and Methodology: The implementation methods include hands-on practice in making decoupage crafts from household waste, such as used bottles and cans, legal counseling on consumer protection, and intensive communication with partners to ensure the program's sustainability. A participatory approach is used to help participants learn in an applicable and independent manner. Findings and Discussion: The activity increased participants' knowledge and skills in processing household waste into products of economic value through decoupage techniques. In addition, participants' understanding of the rights and obligations of business actors and consumer protection mechanisms also increased. The participants' enthusiasm showed that the program was in line with the community's needs and had potential for further development. Implications: This program provides practical benefits, including creative business opportunities that can support the household economy. From a managerial perspective, the results of these activities can serve as a basis for establishing small business groups based on PKK (Family Welfare Movement) and for encouraging further training in areas such as digital marketing and product branding.